Transcriptome analysis of liver elucidates key immune-related pathways in Nile tilapia Oreochromis niloticus following infection with tilapia lake virus. Issue 111 (April 2021) - Sood, Neeraj; Verma, Dev Kumar; Paria, Anutosh; Yadav, Shrish Chandra; Yadav, Manoj Kumar; Bedekar, Megha Kadam; Kumar, Saurav; Swaminathan, Thangaraj Raja; Mohan, Chadag Vishnumurthy; Rajendran, KV; Pradhan, Pravata Kumar
Abstract: Nile tilapia ( Oreochromis niloticus ) is one of the most important aquaculture species farmed worldwide. However, the recent emergence of tilapia lake virus (TiLV) disease, also known as syncytial hepatitis of tilapia, has threatened the global tilapia industry. To gain more insight regarding the host response against the disease, the transcriptional profiles of liver in experimentally-infected and control tilapia were compared. Analysis of RNA-Seq data identified 4640 differentially expressed genes (DEGs), which were involved among others in antigen processing and presentation, MAPK, apoptosis, necroptosis, chemokine signaling, interferon, NF-kB, acute phase response and JAK-STAT pathways. Enhanced expression of most of the DEGs in the above pathways suggests an attempt by tilapia to resist TiLV infection. However, upregulation of some of the key genes such as BCL2L1 in apoptosis pathway; NFKBIA in NF-kB pathway; TRFC in acute phase response; and SOCS, EPOR, PI3K and AKT in JAK-STAT pathway and downregulation of the genes, namely MAP3K7 in MAPK pathway; IFIT1 in interferon; and TRIM25 in NF-kB pathway suggested that TiLV was able to subvert the host immune response to successfully establish the infection. The study offers novel insights into the cellular functions that are affected following TiLV infection and will serve as a valuable genomic resource towards our understanding of susceptibility of tilapia to TiLV infection. Highlights: RNA-Seq data from liver of TilV infected tilapia revealed 4640 differentially expressed genes (DEGs). DEGs belonged to antigen processing and presentation, MAPK, apoptosis, Necroptosis, NF-kB and JAK-STAT pathways. There was downregulation of MAP3K7, IFIT1 and TRIM25 following TiLV infection. Upregulation of genes, namely BCL2L1, NFKBIA, TRFC, SOCS, EPOR, PI3K and AKT was observed. Modulation of key genes suggested that TiLV was able to subvert the host immune response to establish the infection.